PENGUATAN KELUARGA SAKINAH BAGI IBU MUDA DI KECAMATAN UMBULHARJO KOTA YOGYAKARTA - Desy Aniqotsunainy (Jurnal Al-Manar, 2017)
This study is a community service program that is specifically focused on strengthening the harmonious family for young mothers and character building as a model of religious education improvement activities in the District Umbulharjo. Departing from the condition that the focus of the high divorce rate in the city of Yogyakarta District of Umbulharjo which are urban areas from year to year shows the highest number compared to other districts of the city. This study is a participatory action research (PAR) is the research followed by action strengthening harmonious family for young mothers in the district Umbulharjo, with data collection using the method of observation and interviews, then to secondary data such as records and reporting program to improve education marital target area, Data obtained by the search in the area of research. Results devotion focused on the action in an effort to strengthen harmonious family models pioneered by building awareness through open space for dialogue between the views of young mothers that are counterproductive to the goal of marriage, views more positive for the creation of a harmonious family. At the end of synergic cooperation in order to provide stimulus, so existing models harmonious family strengthening of the concept, and their coaching program post-marry so, young mothers will be optimized functions to be integrated community development center.